2017
DOI: 10.4103/ijdr.ijdr_415_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gray values of cone-beam computed tomography with hounsfield units of multislice computed tomography: An in vitro study

Abstract: The gray value for hypodense structures in large volume CBCT scan was more reliable and analogous to HU value in MSCT. The determination of grey values in CBCT may not be as accurate as HU value in CT for hyperdense structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Patrick et al . [ 11 ] in the year 2017 evaluated the correlation between Hounsfield units of multislice computed tomography (MSCT) scans and greyscale values in CBCT in various fields of view for hyperdense as well as hypodense structures. It was found that the grey values for hypodense structures in large-volume CBCT scans were more reliable and analogous to Hounsfield units in MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Patrick et al . [ 11 ] in the year 2017 evaluated the correlation between Hounsfield units of multislice computed tomography (MSCT) scans and greyscale values in CBCT in various fields of view for hyperdense as well as hypodense structures. It was found that the grey values for hypodense structures in large-volume CBCT scans were more reliable and analogous to Hounsfield units in MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, the subjectively chosen grey values 201 and lower to measure the volume, marginal and internal void are arguable. These grey values are more reliable in CBCT than Hounsfield Units [36, 37]. But small movements of the model in the CBCT resulted in small deviant grey values.…”
Section: Discussionmentioning
confidence: 99%
“…The corridor’s dimensions were defined to allow screw positioning if that bore probe with a diameter of 7.5 mm would not affect surrounding cortical bone along the corridor except for the entry and exit points. Affecting cortical bone was defined by exceeding a threshold of 400 HU 27 29 . This calculation was performed on the overall mean model and on both pubic ramus of all bone models resulting in a total of 300 individual bore probes available for evaluation.…”
Section: Methodsmentioning
confidence: 99%